Analisis Kesalahan Kalimat Berimbuhan Dalam Teks Narasi Karangan Siswa Pada Pembelajaran Bahasa Indonesia Di Kelas IV SD Yasporbi III Pasar Minggu Jakarta Selatan - Vika Bunga; Robiatul Munajah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study is to provide an investigation of affixing sentence mistakes in narrative text essays written by fourth graders. In addition, we want to detail the challenges that both students and instructors have when attempting to convey the concept of affixing sentences to elementary school children. A case study is the research approach that is used. In this study, a descriptive example is used. The 70 participants in this research were drawn from three different classes (A, B, and C) and one larger class (22–24 students) at SD YASPORBI III Jakarta, representing Class IV as a whole. This study used a random sampling approach. Research tools used in this study were observation and interview tools. Observation, interviews, and documentation are the methods used to gather data in this study. There were four steps to the analytic process in this study: gathering data, cleaning it up, presenting it, and making conclusions. Study after study has shown that students retain more information and are more actively involved in their own learning when taught about affixes via the use of narrative process that incorporates anecdotes from real life. Teachers may help children who are still struggling with affix sentence writing by using narrative texts to gather often misused terms, such as capital and lowercase letters, which are connected to spelling and spelling comprehension. Teachers should thus provide their pupils with more support and assistance, whether that's in the form of extra explanations, specific activities, or both. Students have a more engaging and effective learning experience when visuals are used as a medium.